Rare copy number variants in ASTN2 gene in patients with neurodevelopmental disorders. (17th August 2021) - Bauleo, Alessia; Montesanto, Alberto; Pace, Vincenza; Brando, Rossella; De Stefano, Laura; Puntorieri, Domenica; Cento, Luca; Loddo, Sara; Calacci, Chiara; Novelli, Antonio; Falcone, Elena
Abstract : Introduction: In humans the normal development of cortical regions depends on the complex interactions between a number of proteins that promote the migrations of neuronal precursors from germinal zones and assembly into neuronal laminae. ASTN2 is one of the proteins implicated in such a complex process. Recently it has been observed that ASTN2 also regulates the surface expression of multiple synaptic proteins resulting in a modulation of synaptic activity. Several rare copy number variants (CNVs) in ASTN2 gene were identified in patients with neurodevelopmental disorders (NDDs) including autism spectrum disorders (ASD), attention deficit–hyperactivity disorders and intellectual disability. Methods: By using comparative genomic hybridization array technology, we analyzed the genomic profiles of five patients of three unrelated families with NDDs. Clinical diagnosis of ASD was established according to the Statistical Manual of Mental Disorders, Fifth Edition (APA 2013) criteria. Results: We identified new rare CNVs encompassing ASTN2 gene in three unrelated families with different clinical phenotypes of NDDs. In particular, we identified a deletion of about 70 Kb encompassing intron 19, a 186 Kb duplication encompassing the sequence between the 5′-end and the first intron of the gene and a 205 Kb deletion encompassing exons 6–11. Conclusion: The CNVs reported here involve regions not usually disrupted in patients with NDDs with two of them affecting only the expression of the long isoforms. Further studies will be needed to analyze the impact of these CNVs on gene expression regulation and to better understand their impact on the protein function.